Pemanfaatan Media Power Point terhadap Tingkat Konsentrasi dan Motivasi Belajar Peserta Didik - Budi Sulistiyo Nugroho; Zahraini Zahraini; Hidayatus Sholihah; Salfin Salfin; Maryana Maryana; Sufyan Hakim (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of using Power Point media on the level of concentration and motivation of students. The research method used in this study is a literature study by collecting data from various reliable sources. The analysis results show that the use of Power Point media can increase the concentration and motivation of students. This is because Power Point has an attractive and interactive appearance, which can attract the attention of students and make them more focused on learning. In addition, the use of Power Point can also facilitate students in understanding the material presented by teachers or lecturers. Therefore, the use of Power Point media is highly recommended in learning to improve the quality of student learning